Subdosages of Bacillus thuringiensis on Plutella xylostella) (Lepepidoptera: plutellidae) and Trichogramma pretiosum (Hymenoptera: trichogrammatidae) - De Bortoli, Sergio Antonio [UNESP]; Vacari, Alessandra Marieli [UNESP]; De Magalhaes, Gustavo Oliveira [UNESP]; Dibelli, Wanderlei [UNESP]; De Bortoli, Caroline Placidi [UNESP]; Alves, Murilo Petrini [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2012)
The aim of this paper was to evaluate the biological aspects of Plutella xylostella and Trichogramma pretiosum in eggs of the F2 generation of P. xylostella under the influence of Bacillus thuringiensis in laboratory conditions. The experiment was conducted in the Laboratorio de Biologia and Criacao de Insetos of Faculdade de Ciencias Agrarias e Veterinarias de Jaboticabal - UNESP reen collars contaminated with strains and commercial product based on B. thuringiensis in the laboratory. The eggs obtained from the F2 generation of P. xylostella evaluated the biological parameters of T. pretiosum. It was observed that some biological characteristics of P. xylostella showed changes by the treatment with B. thuringiensis. The viability of the larvae and pupae stages, pupae weight were the biological parameters more influenced by treatments, with values significantly reduced when compared to control. However, the larvae length and pupae stages and sex ratio were similar in all treatments, with no significant biological variations. Thus, this bacterium isolated from this behavior may provide greater exposure of larvae to other natural enemies as well as generation of adults less viable, which makes them potential programs in pest control, since the interaction of the methods of control is one of the main ways to enhance the biological control of insect pests. It was observed sublethal effects on P. xylostella biology, and B. thuringiensis negative influence on the parasitism capacity and emergency of T. pretiosum.

O objetivo desta pesquisa foi avaliar aspectos biológicos de Plutella xylostella e de Trichogramma pretiosum em ovos de P. xylostella sob a influência de Bacillus thuringiensis em condições de laboratório. O experimento foi desenvolvido no Laboratório de Biologia e Criação de Insetos da Faculdade de Ciências Agrárias e Veterinárias de Jaboticabal – UNESP, utilizando-se delineamento inteiramente casualizado com 60 repetições. Para tanto, avaliou-se a biologia de P. xylostella em Brassica oleracea var. acephala (couve Manteiga) contaminada com isolados, linhagem e produto comercial a base de B. thuringiensis. A partir dos ovos obtidos da geração F2 de P. xylostella avaliaram-se os parâmetros biológicos de T. pretiosum. Observou-se que algumas características biológicas de P. xylostella apresentaram alterações mediante aos tratamentos com B. thuringiensis. A viabilidade larval e pupal, e o peso de pupas foram os parâmetros biológicos que mais sofreram influências dos tratamentos, com valores reduzidos significativamente em relação à testemunha. Já, as durações das fases de larva e de pupa, além da razão sexual, foram semelhantes em todos os tratamentos, não apresentando variações biológicas. Dessa forma, isolados desta bactéria com este comportamento podem proporcionar maior exposição das lagartas a outros inimigos naturais, bem como geração de adultos menos viáveis, o que os torna com potencial em programas de controle de pragas. Observou-se a existência de efeitos subletais na biologia de P. xylostella; e influência do B. thuringiensis na capacidade de parasitismo e de emergência de T. pretiosum.
Subdosagens de Bacillus thuringiensis em Plutella xylostella (Lepidoptera: plutellidae) e Trichogramma pretiosum (Hymenoptera: trichogrammatidae)
Keywords: Microbial control; Entomopathogenous; Diamondback moth